Comparison of biomechanical and anthropometrical data of Nigeria tertiary institution students with some selected countries - S.O. Ismaila; S. B. Adejuyigbe; A.I. Musa; O.D. Akinyemi; M.S. Abolarin (Management Science Letters, 2012)
The anthropometric data of student in selected tertiary institutions in Abeokuta, Ogun State, Nigeria was investigated and this was compared with some selected foreign countries. The study was to determine whether design improvement and further study is required in order to improve the conditions in Nigeria tertiary institutions. The anthropometrics measurements data were collected from 720 students of selected institutions. The data indicate a substantial degree of variability between the Nigerian tertiary students’ body and the foreign counterparts. Since most of the furniture in use in our tertiary institutions in Abeokuta, Nigeria were designed and constructed using the anthropometric data of students in foreign countries, there is need for anthropometric data of Nigerian students in the tertiary institution for the design and construction of furniture to suit them. The result is of great concern which could affect students in other institutions throughout Nigeria and could also pose a great risk of having back problem among students in Nigeria. Statement of Relevancy: The chair and table used in Nigeria were designed with reference to the measurement of other countries. The database of the Nigerian students will be very useful parameter in guiding principle for the designing of future equipment to be used in classrooms, laboratories and lecture theaters of the institutions.